1987
DOI: 10.1152/jappl.1987.63.3.969
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial pressure-flow plots in dogs: effects of isoflurane and nitroprusside

Abstract: We investigated the effects of nitroprusside and isoflurane on multipoint pulmonary arterial pressure (PAP)/cardiac index (Q) plots in pentobarbital sodium-anesthetized dogs ventilated alternatively in hyperoxia (fraction of inspired O2, FIO2, 0.4) and hypoxia (FIO2 0.1). Over the entire range of Q studied, 2-5 l.min-1.m-2, hypoxia increased PAP in 16 dogs ("responders") and did not affect PAP in 16 other dogs ("nonresponders"). A hypoxic pulmonary vasoconstriction (HPV) was restored in the nonresponders by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…21 In previous studies, isoflurane was found to cause some increase or no change in pulmonary vascular tone. 10,17,20,22 Heerdt et al 11 reported that PA resistance and elastance were increased with isoflurane, in contrast with aortic resistance that decreased and aortic elastance that remained unchanged. In the current study, isoflurane and desflurane reduced PA pressure.…”
Section: Discussionmentioning
confidence: 99%
“…21 In previous studies, isoflurane was found to cause some increase or no change in pulmonary vascular tone. 10,17,20,22 Heerdt et al 11 reported that PA resistance and elastance were increased with isoflurane, in contrast with aortic resistance that decreased and aortic elastance that remained unchanged. In the current study, isoflurane and desflurane reduced PA pressure.…”
Section: Discussionmentioning
confidence: 99%
“…SNP inhibited the hypoxic pulmonary vasoconstriction in anaesthetized dogs [20]. Moreover, the NO donor was an effective vasodilator of all pulmonary vessels with the exception of the smallest arteries in a model of sheep isolated pulmonary arteries and veins [21].…”
Section: L-namementioning
confidence: 88%
“…Flow-pressure relations better discriminate between passive (flow-induced) changes and active (tone-induced) changes in PA pressure, and allow detection of more subtle changes in vascular tone. 24 Flow-pressure curves here were generated with transient flow reductions (less than 10 s) to prevent cardiovascular responses because of sympathetic activation. 18 Pulmonary vascular impedance allows for the quantification of the three components that oppose blood ejection from the ventricle into the artery, i.e., resistance because of small distal vessels, elastance because of large proximal vessels, and reflected waves that increase pressure and decrease forward flow.…”
Section: Pulmonary Hemodynamicsmentioning
confidence: 99%